Clinical and Imaging Follow-Up of Patients with Coiled Basilar Tip Aneurysms Up to 20 Years - van Eijck, M.; Bechan, R.S.; Sluzewski, M.; Peluso, J.P.; Roks, G.; van Rooij, W.J. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Long-term follow-up data of coiled basilar tip aneurysms are scarce, and little is known about the risk of late aneurysm-related adverse events. We followed a cohort of 154 patients with basilar tip aneurysms coiled between 1995 and 2006.MATERIALS AND METHODS: Imaging and clinical data were retrospectively reviewed. The incidence and timing of retreatment, rebleeds, and progressive mass effect by continuous aneurysm growth were recorded. Risk factors for retreatment were assessed.RESULTS: Clinical follow-up of 144 of 154 patients who survived the admission period was a mean of 9.8 years (median, 10.2; range, 0.3–20.1 years). During this period, 37 basilar tip aneurysms (26%) were additionally coiled (annual incidence rate, 2.6%; 95% CI, 1.8%–3.6%). Aneurysm size of >15 mm was the most important independent predictor for retreatment (OR, 8.7; 95% CI, 3.4–22.5). The first additional coiling was performed in the first year of follow-up in 17 of 37 patients (46%) and in 20 patients (54%) at a later time up to 17.2 years. Nine rebleeds occurred in 9 of 106 patients who initially presented with SAH after a median follow-up of 8.3 years (range, 0.3–16.6 years). The annual incidence rate was 0.7% (95% CI, 0.4%–1.5%). Eight patients died of aneurysm-related adverse events: 3 of rebleed and 5 of progressive mass effect.CONCLUSIONS: Retreatment of coiled basilar tip aneurysms was frequently needed during follow-up, also at long intervals. Most late mortality was from progressive mass effect, not from rebleeds. Life-long MRA follow-up at yearly intervals is recommended.